Non-sebaceous Lymphadenoma of the Parotid Gland Mimicking a Pleomorphic Adenoma - Carlos Antonio Morales Morales; Alan Ellison Ramos Mayo; Mauricio Gonzalez-Urquijo; Álvaro Barbosa Quintana; Eduardo Alberto Guzmán Huerta (SAGE Publishing, 2021)
Non-sebaceous lymphadenoma of the salivary glands is a rare benign lesion, first described in 1991. We present the case of a 54-year-old woman, with a right parotid mass. She underwent right superficial parotidectomy, and histopathology reported a non-sebaceous lymphadenoma due to an encapsulated lesion and multiple non-atypical epithelial inclusions without sebaceous differentiation. The etiology of non-sebaceous lymphadenoma is not yet understood, but it can arise predominantly from the parotid gland. Surgical excision is the treatment of choice.